2005
DOI: 10.1007/s00439-005-1297-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genealogical characterization of the R1443X BRCA1 mutation in high-risk French-Canadian breast/ovarian cancer families

Abstract: The Quebec population contains about six-million French Canadians, descended from the French settlers who colonized "Nouvelle-France" between 1608 and 1765. Although the relative genetic contribution of each of these founders is highly variable, altogether they account for the major part of the contemporary French-Canadian gene pool. This study was designed to analyze the role of this founder effect in the introduction and diffusion of the BRCA1 recurrent R1443X mutant allele. A highly conserved haplotype, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 41 publications
(39 reference statements)
4
43
0
2
Order By: Relevance
“…Mutations c.4065_4068del4 and p.Arg1443X were found in Sweden [31], p.Arg1443X in the Sicilian population [26] as well as in the French population as a founder mutation [32]. Other Slovak low frequency BRCA1 pathogenic mutations were not occuring in any European HBOC report.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 85%
“…Mutations c.4065_4068del4 and p.Arg1443X were found in Sweden [31], p.Arg1443X in the Sicilian population [26] as well as in the French population as a founder mutation [32]. Other Slovak low frequency BRCA1 pathogenic mutations were not occuring in any European HBOC report.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 85%
“…BRCA1-interacting gene variants in BOC families F Guénard et al have to keep in mind that the greater extent of LD generally found in the French Canadian population can be responsible for a lower number of haplotype blocks. 56 In addition such a difference between HapMap and this study may be due to the higher coverage of the gene regions in the HapMap data set which include both exonic and intronic SNPs, the latter not assessed in our study. The analysis of the coding region of the AURKA, BAP1, BARD1 and DHX9 genes did not identify any deleterious truncating mutation or aberrant splicing mRNAs.…”
Section: Brca1-interacting Gene Variants In Boc Families F Guénard Et Almentioning
confidence: 89%
“…Ethnic origin of some BRCA mutation described in Latin American countries has been confirmed as Jewish (c.68 69delAG) [70], Spanish (BRCA1 c.211A>G and BRCA2 c.2808 2811del4), Portuguese (BRCA2 c.156 157insAlu), Irish (BRCA2 c.5946delT), Baltic-zone origin (BRCA1 c.5266dupC) [21], French (BRCA1, c.4327C>T and BRCA1 4945 4947delAGAinsTTTT) [71], Sudafrican and African-American (c.5324T>G and c.824 825insAGCCATGTGG in BRCA1, and c.1310 1313delAAGA and c.3365 3366delCA in BRCA2) [72].…”
Section: Clinicomolecular Features Of Hostmentioning
confidence: 92%